PIP2 Improves Cerebral Blood Flow in a Mouse Model of Alzheimer's Disease. Issue 2 (22nd February 2021) - Mughal, Amreen; Harraz, Osama F; Gonzales, Albert L; Hill-Eubanks, David; Nelson, Mark T
Abstract: Alzheimer's disease (AD) is a leading cause of dementia and a substantial healthcare burden. Despite this, few treatment options are available for controlling AD symptoms. Notably, neuronal activity-dependent increases in cortical cerebral blood flow (CBF; functional hyperemia) are attenuated in AD patients, but the associated pathological mechanisms are not fully understood at the molecular level. A fundamental mechanism underlying functional hyperemia is activation of capillary endothelial inward-rectifying K + (Kir2.1) channels by neuronally derived potassium (K + ), which evokes a retrograde capillary-to-arteriole electrical signal that dilates upstream arterioles, increasing blood delivery to downstream active regions. Here, using a mouse model of familial AD (5xFAD), we tested whether this impairment in functional hyperemia is attributable to reduced activity of capillary Kir2.1 channels. In vivo CBF measurements revealed significant reductions in whisker stimulation (WS)-induced and K + -induced hyperemic responses in 5xFAD mice compared with age-matched controls. Notably, measurements of whole-cell currents in freshly isolated 5xFAD capillary endothelial cells showed that Kir2.1 current density was profoundly reduced, suggesting a defect in Kir2.1 function. Because Kir2.1 activity absolutely depends on binding of phosphatidylinositol 4, 5-bisphosphate (PIP2 ) to the channel, we hypothesized that capillary Kir2.1 channel impairment could be corrected by exogenously supplying PIP2 . As predicted, a PIP2 analog restored Kir2.1 current density to control levels. More importantly, systemic administration of PIP2 restored K + -induced CBF increases and WS-induced functional hyperemic responses in 5xFAD mice. Collectively, these data provide evidence that PIP2 -mediated restoration of capillary endothelial Kir2.1 function improves neurovascular coupling and CBF in the setting of AD. :